FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR (Studi Empiris Pada KAP Se-Jawa Tengah Dan DIY) - Genta Satria Prabowo, 13.05.52.0072; Badjuri, Achmad (Students Journal of Accounting and Banking, 2017)
This study aimed to examine the effect of Professionalism, organizational culture, organizational commitment, motivation, professional ethics, style of leadership and independence which directly affects the performance of the auditors. The population in this study were all auditors working in the public accounting firm in Central Java and Yogyakarta. Sampling was done by using purposive sampling method and sample size were 91 respondents. The primary data collection method used is the questionnaire. Data were analyzed using multiple linear regression model. Result of research indicate that the variables: professionalism, organizational culture, organizational commitment, motivation, professional ethics, leadership style and independence have significant positive effect to performance of auditors.Keywords:Â Professionalism, Organizational Culture, Organizational Commitment, Motivation, Professional Ethics, Leadership Style and Independence